Establishing a baseline for surgical care in Mongolia: a situational analysis using the six indicators from the Lancet Commission on Global Surgery - Raymond R Price; Ali Jalali; Anudari Zorigtbaatar; Sarnai Erdene; Sergelen Orgoi; Andrea Davis; Jonathan Nellermoe; Jade M Nunez; Simon Ruhnke; Battsetseg Gonchigjav; Nomindari Bat-Erdene; Kevin Bagley; et al. (BMJ Open)
Objectives To inform national planning, six indicators posed by the Lancet Commission on Global Surgery were collected for the Mongolian surgical system. This situational analysis shows one lower middle-income country’s ability to collect the indicators aided by a well-developed health information system.Design An 11-year retrospective analysis of the Mongolian surgical system using data from the Health Development Center, National Statistics Office and Household Socio-Economic Survey. Access estimates were based on travel time to capable hospitals. Provider density, surgical volume and postoperative mortality were calculated at national and regional levels. Protection against impoverishing and catastrophic expenditures was assessed against standard out-of-pocket expenditure at government hospitals for individual operations.Setting Mongolia’s 81 public hospitals with surgical capability, including tertiary, secondary and primary/secondary facilities.Participants All operative patients in Mongolia’s public hospitals, 2006–2016.Primary and secondary outcome measures Primary outcomes were national-level results of the indicators. Secondary outcomes include regional access; surgeons, anaesthesiologists and obstetricians (SAO) density; surgical volume; and perioperative mortality.Results In 2016, 80.1% of the population had 2-hour access to essential surgery, including 60% of those outside the capital. SAO density was 47.4/100 000 population. A coding change increased surgical volume to 5784/100 000 population, and in-hospital mortality decreased from 0.27% to 0.14%. All households were financially protected from caesarean section. Appendectomy carried 99.4% and 98.4% protection, external femur fixation carried 75.4% and 50.7% protection from impoverishing and catastrophic expenditures, respectively. Laparoscopic cholecystectomy carried 42.9% protection from both.Conclusions Mongolia meets national benchmarks for access, provider density, surgical volume and postoperative mortality with notable limitations. Significant disparities exist between regions. Unequal access may be efficiently addressed by strengthening or building key district hospitals in population-dense areas. Increased financial protections are needed for operations involving hardware or technology. Ongoing monitoring and evaluation will support the development of context-specific interventions to improve surgical care in Mongolia.